A room for design: Through participatory design young adults with schizophrenia become strong collaborators. (13th June 2016) - Terp, Malene; Laursen, Birgitte Schantz; Jørgensen, Rikke; Mainz, Jan; Bjørnes, Charlotte D.
Abstract: Smartphone technology is being increasingly viewed as key to engaging young adults with schizophrenia in their own mental health care. In an attempt to use smartphones as an engagement tool, we conducted a participatory design process, where young adults with schizophrenia ( n  = 4), healthcare providers ( n  = 7), software designers ( n  = 3), graphic designer ( n  = 1), graphic recorder ( n  = 1), and team leader ( n  = 1) co‐designed a smartphone application for use in early phase schizophrenia care. This paper reports the co‐design process. Based on a variety of written data‐sources, the paper describes if, and how, participatory design can help construct a physical and relational environment that enables young adults with schizophrenia to become active participants in the design of a more participatory mental health practice. Guided by Etienne Wenger's construct of Community of Practice, three major categories of characteristics and construction of a physical and relational environment supporting and inspiring participation and engagement were identified: (i) a pre‐narrative about a community of practice, (ii) the room for design is a community of practice and (iii) the community of practice as a practice of special qualities. It is concluded that participatory design can support and inspire participation and engagement in the development of mental health care with young adults with schizophrenia, given that the environment in which participatory design unfolds is transparent, flexible, secure and informal.